2018
DOI: 10.1051/matecconf/201815602015
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer Coefficient of Ozone in a Bubble Column

Abstract: Abstract. The effect of flow rate of ozone-containing gas and pH on the mass transfer coefficient of ozone through water in a bubble column reactor has been studied. Ozone was generated from air using a corona discharge ozone generator. The flow rate of air was varied from 2 to 5 L min -1 , while pH was varied from 4 to 10. The gas containing ozone was bubbled to the reactor containing 1.5 L of 2% KI solution. The temperature was set at 281C. The concentration of ozone was determined using titrimetric method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…The mass transfer coefficients obtained were of the same order of magnitude as those found by other authors [23,30,31], emphasizing the significant increase at pH = 7.0, where Rodríguez et al [23] obtained a coefficient of 0.073 min −1 .…”
Section: Ozone Kinetic Mass Transfer Modellingsupporting
confidence: 85%
“…The mass transfer coefficients obtained were of the same order of magnitude as those found by other authors [23,30,31], emphasizing the significant increase at pH = 7.0, where Rodríguez et al [23] obtained a coefficient of 0.073 min −1 .…”
Section: Ozone Kinetic Mass Transfer Modellingsupporting
confidence: 85%
“…Physical observation clearly showed that the bubbles produced in 2‐L/min flow rate were finer than those produced in 1.2‐L/min flow rate. Therefore, a high concentration of O 3 at a flow rate of 2‐L/min flow is expected to produce a small gas bubble through a 2‐mm fine ozone nozzle and maximize the O 3 solubility into the sample through gas–liquid films, as mentioned in the two film theories (Ratnawati et al, 2018). Lage Filho (2010) pointed out that fine bubbles present a large surface area for O 3 gas to be transferred or dissolved in the liquid phase.…”
Section: Resultsmentioning
confidence: 99%
“…Lage Filho (2010) pointed out that fine bubbles present a large surface area for O 3 gas to be transferred or dissolved in the liquid phase. This phenomenon can be described in Equation (Ratnawati et al, 2018). italicdC/italicdtgoodbreak=italickLa0.25em()C*goodbreak−C, where kLa is the volumetric mass transfer coefficient of ozone, and C and C * are the concentrations of ozone at time t and at saturated conditions, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results indicated that the helical structure of the hollow fibers of the ozone–liquid membrane contactor contributed to the high ozone flow rates and high ozone dissolved concentration, increasing the mass transfer coefficient. Ratnawati et al 28 studied the effect of the ozone-containing gas flow rate (over a range of 2–5 L min −1 ) and pH (over a range of 4–10) on the ozone mass transfer coefficient in a bubble column reactor. The obtained results indicated that a maximum K L a of 2.1 × 10 −3 s −1 at pH 4 with a gas flow rate of 4 L min −1 was obtained.…”
Section: Overview Of Work Done On the Intensification Of Ozone–liquid...mentioning
confidence: 99%